EVALUASI KARAKTER KOMPAK HASIL PENGUJIAN KETURUNAN SIKLUS KETIGA PROGRAM PEMULIAAN KELAPA SAWIT PUSAT PENELITIAN KELAPA SAWIT - Ikhwan Fadli Pangaribuan; Yurna Yenni; Sujadi Sujadi; Edy Suprianto (Jurnal Penelitian Kelapa Sawit, 2019)
One of the secondary characters desired by oil palm planters is compact palm. Compact characters are characterized by slow height increment rate and short rachis length. Both characters are able to extend the economic life of oil palm and increase palm productivity. This paper will discuss the results of the evaluation of compact characters in several crosses of the third cycle progeny test of RRS (Reciprocal Recurrent Selection) program. The field trial was carried out on 21 crosses planted in 2008 at Dolok Sinumbah Estate. The observations showed that cross no. BJ62/05 and BJ05/05 have the potential to produce compact palm with the slowest height increment rates, the shortest rachis, and low LAI values. With these characters, these crosses can be planted at higher planting densities. Parents no. BJ5633D and 93-133-4T also have the potential to produce offspring with compact characters.